Síndrome de burnout nos enfermeiros e agentes comunitários de saúde das unidades básicas de saúde do município de Assú-RN - Medeiros, Elyza Raquel dos Santos (Universidade Federal Rural do Semi-Árido, 2017)
The world of work is in constant process of changes, which entail deep, increasingly complex demands on the professionals in action. This causes stress, tension and physical and emotional exhaustion, which directly affect the individual. When this stress becomes excessive, it can happen to the scam - in this case, known as burnout syndrome or SB, which affects the quality of service provided. In the health area, due to the nature and characteristics of the work, its professionals are more susceptible to a high level of occupational stress. In this way the professionals of this area present strong tendencies to develop Burnout syndrome (SB). Therefore, the objective of this study was to analyze the relationship between the factors related to the tasks, the norms and processes, the interpersonal relations and the individual, with the prevalence of the burnout syndrome in the nurses and in the community health agents of the Units Health Units (BHU) in the municipality of Assu-RN. To do so, two instruments were applied: the Maslach Burnout Inventory (MBI) and the Socio-Functional Questionnaire (QSF), adapted from Carneiro (2010), with 98 participants, 17 nurses and 81 ACS. The analysis was quantitative, using descriptive statistics and Pearson's correlation, with the aid of the SPSS. The results indicate that 12.92% of those investigated have a high tendency to develop SB, while another 31.63% have a moderate tendency and 55.45% have a low tendency to develop it. In addition, the results of the correlation analysis show that there is a relationship between some individual, social, functional and institutional factors with SB prevalence.
Monografia
Keywords: Síndrome de Burnout; Enfermeiros; Agentes Comunitários de Saúde; Burnout Syndrome; Nurses; Community Health Agents; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO